Controlling Interconnected Silver Network Structure in Sol–Gel Nanocomposite Via Shrinkage‐Induced Stress. Issue 1 (27th August 2012) - Chiu, Chi‐Kai; Chen, Tsan‐Yao; Luo, Tzy‐Jiun M.
Abstract An interconnected silver network composed of grain boundary layers with each layer about 100 nm thick was spontaneously formed inside a silica matrix when a sol–gel sample containing silver ion and polyethylene glycol was dried and heat‐treated. The minimum spacing of the silver structure was ≈15 µm and the density of the silver structure was related to the drying rate, which can be controlled by either drying temperature or vacuum drying time. It was found that the shrinkage‐induced stress during the drying process results in microcracks where the crack surfaces serve as a 3D template for silver to develop into interconnected network when the sample is annealed at 160 °C. The ability to control the density of microcracks and to utilize the microcracks as silver template suggests that this method can be utilized to (1) create interconnected silver network of desired density in silica materials, (2) visualize the microcracks of sol–gel materials, and (3) reinforce and repair the defects after microcracks have formed.